Diskursanalytische Geschlechterforschung in der Erziehungswissenschaft - Fegter, Susann; Langer, Antje; Thon, Christine (Jahrbuch erziehungswissenschaftliche Geschlechterforschung, 2021)
Poststructuralist and discourse theoretical approaches are of growing importance for gender studies in education and are accompanied by an increasing implementation of discourse analytical methodologies. The contributions in this volume take up the wide range of topics that discourse analytical approaches currently address in educational gender studies and provide impulses for a systematizing reflection on the different theories of discourse, subjectivation and methods that are used in this field.